Investigation on microgrid control for grid tied PV battery system incorporating sustainable manufacturing technology. (2021) - Dharmalingam, K.N.; Nalini, A.; Jijina, G.O.; Sheeba Percis, E.; Jenish, T.; Jayarajan, J.; Sendilvelan, S.
Abstract: In today's scenario, the Sustainable Manufacturing has become vital due to the increase in expense of conventional resources. The awareness on the pollution causing factors to have risen under societal pressure which emphasize on recycling the waste thereby reducing the pollution. Therefore, power generation using sustainable technology has gained momentum all over the world and in a developing nation like India which is also blessed with sunlight throughout the year, this sustainable power generation has taken its place and a proper control strategy to operate the system effectively is needed. In this paper investigation is done on a three-phase utility interfaced Microgrid system by applying Optimum Filtering Theory Control. The Microgrid is incorporated with the manageable Battery Energy Storage (BES) and Photovoltaic (PV) cluster at DC transport of voltage source converter (VSC) to save capacity efficiently for the nearby loads and conveyance coordinated with improved power quality ability. At present Lithium Ion BES is utilized to improve the security and dependability of PV-BES microgrid framework. The Li-Ion BES isn't just gainful on every day vitality sparing however it is likewise estimated to outfit smoothing offices to the PV-BES microgrid framework. The optimum filtering theory based control is used to control the PV-BES microgrid system in current control mode. The dynamic operation of PV-BES Microgrid system is improved by incorporating the PV Feed Forward (PVFF) in current control for active power injection in the Utility. PV-BES Microgrid Network performance is tested and validated.